The social dimension of the Europe 2020 strategy - A report of the social protection committee (2011) (Luxembourg, 2011)
"he Europe 2020 strategy aims to deliver high employment, productivity and social cohesion. This report of the Social Protection Committee (SPC), a policy forum for Member States and the Commission, on Europe 2020's social dimension examines actions to promote inclusion and reduce poverty. It details the current poverty and social exclusion situation in the EU and assesses related policy options for addressing these challenges. It also outlines findings of the SPC thematic work on social inclusion and protection in 2010. "